Rapid determination of 14 odorous compounds in drinking water using gas chromatography-mass spectrometry coupled with headspace solid-phase microextraction pretreatment. Issue 48 (1st December 2022) - Tong, Xuezhi; Zhang, Hao; Fan, Xiang; Yang, Shengyuan; Chen, Dongyang; Feng, JiaLi; Tan, Shan; Zeng, Dong
Abstract : A sensitive and effective method was developed to detect 14 odorous compounds in water using GC-MS with headspace solid-phase microextraction. Abstract : A sensitive and effective method was developed for the simultaneous determination of 14 odorous compounds in drinking water using gas chromatography-mass spectrometry (GC-MS) coupled with headspace solid phase microextraction (HS-SPME) pretreatment. The influencing factors including SPME fiber, ionic strength, temperature and time on the pretreatment procedure were evaluated systematically. Under the optimized conditions, 10 mL of the samples added with 1.0 g sodium chloride was extracted by CAR/PDMS fiber at 60 °C for 30 min and then desorbed at 280 °C for 3 min. The analytes achieved good linearity as the mass concentrations were in the range of 0.0020–10.0 μg L −1 with correlation coefficients higher than 0.9990. The limits of detection (LODs) ranging between 0.2 and 50 ng L −1 were lower than the olfactory threshold of these studied compounds. Satisfactory recoveries were obtained ranging from 84.8% to 110.6%, and good reproducibility indicated by relative standard deviation (RSD) in the range of 0.50–9.5% was obtained as well. The proposed method was convenient, sensitive and accurate, which was suitable for the routine monitoring 14 odorous compounds in water.